The PANORAMIC Survey: Pure Parallel Wide Area Legacy Imaging with JWST/NIRCam - Christina C. Williams; Pascal A. Oesch; Andrea Weibel; Gabriel Brammer; Aidan P. Cloonan; Katherine E. Whitaker; Laia Barrufet; Rachel Bezanson; Rebecca A. A. Bowler; Pratika Dayal; Marijn Franx; Jenny E. Greene; et al. (The Astrophysical Journal)
We present the PANORAMIC survey, a pure parallel extragalactic imaging program with JWST/NIRCam observed during Cycle 1. The survey obtained ∼530 square arcmin of NIRCam imaging from 1–5 μ m, totaling ∼192 hr of science integration time. This represents the largest on-sky time investment of any Cycle 1 GO extragalactic NIRCam imaging program by nearly a factor of 2. The survey includes ∼432 square arcmin of novel sky area not yet observed with JWST using at least six NIRCam broadband filters, increasing the existing area covered by similar Cycle 1 data by ∼60%. Additionally, 70 square arcmin was also covered by a seventh filter (F410M). A fraction of PANORAMIC data (∼200 square arcmin) was obtained in or around extragalactic deep fields, enhancing their legacy value. Pure parallel observing naturally creates a “wedding cake” survey with both wide and ultra-deep tiers, with 5 σ point-source depths at F444W ranging from 27.8–29.4 (ABmag), and with minimized cosmic variance. The ≳6-filter strategy yields remarkably good photometric redshift performance, achieving similar median scatter and outlier fraction as CANDELS ( σ _NMAD ∼ 0.07; η ∼ 0.2), enabling a wealth of science across redshift without need for follow-up or ancillary data. We overview the proposed survey, the data obtained as part of this program, and document the science-ready data products in the data release. PANORAMIC has delivered wide-area and deep imaging with excellent photometric performance, demonstrating that pure parallel observations with JWST are a highly efficient observing mode that is key to acquiring a complete picture of galaxy evolution from rare bright galaxies to fainter, more abundant sources across redshifts.